Causal relationship between immune factors and Guillain-Barré syndrome - Taichuan Xu; Xingguo Zhang; Xianfa Xu; Wentao Xiao; Wenjie Li; Xian Zhang (Medicine, 2026)
Guillain-Barré syndrome (GBS) is an immune-mediated polyneurogenic disorder that is strongly correlated with immune factors. However, causal relationships between these factors remain unclear. We used 2-sample Mendelian randomization (MR) and inverse MR analysis. Immune factors were used as the outcome for GBS exposure. Cochrane Q test was used to detect heterogeneity. Simultaneously, the MR-Egger intercept test and MR-Pleiotropy Residual Sum and Outlier tests were used to check for horizontal pleiotropy. MR Steiger was used to estimate the direction of causal inference when the instrumental variables were insufficient in inverse MR. Eighteen immune traits and 1 inflammatory protein were identified as causally involved in the risk of GBS. Reverse MR revealed that GBS was correlated with the levels of eleven immune traits. The sensitivity analyses did not identify any potential heterogeneity or horizontal pleiotropy. Steiger did not find any evidence of reverse causation. We used 2-sample MR to investigate the causal relationship between immune factors and GBS, and our results provide clues for further research.